1981
DOI: 10.1346/ccmn.1981.0290510
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Study of Types of Water Associated with Clinoptilolite

Abstract: Abstract--The identification and quantification of the water associated with powdered clinoptilolite and clinoptilolite-bearing tufts were made using thermogravimetric, vacuum gravimetric, and differential scanning calorimetric techniques. Inflection points on thermogravimetric curves at approximately 80 ~ and 170~ correspond to changes in the proportions of externally adsorbed water to loosely bound zeolitic water and loosely bound zeolitic water to tightly bound zeolitic water, respectively. These three type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 16 publications
9
54
1
Order By: Relevance
“…In the temperature range of >200 °C, both adsorbents show negligible mass losses, thus indicating reasonable thermal stability at elevated temperature. This is in agreement with the results of Knowlton and White [28] where it was reported that there are at least three types of water present in zeolites: crystal water, loosely bound water and tightly held water. The first two were reported to be easily removed within the temperature range of 50-200 °C.…”
Section: Bet and Sem Analysissupporting
confidence: 93%
“…In the temperature range of >200 °C, both adsorbents show negligible mass losses, thus indicating reasonable thermal stability at elevated temperature. This is in agreement with the results of Knowlton and White [28] where it was reported that there are at least three types of water present in zeolites: crystal water, loosely bound water and tightly held water. The first two were reported to be easily removed within the temperature range of 50-200 °C.…”
Section: Bet and Sem Analysissupporting
confidence: 93%
“…4 were integrated to find the energy required for this process. 158-336 J/g energy was absorbed as reported in Table 1, due to mainly evaporation of free water and slightly bound water [15] or water in the mesopores of the fibers [16].…”
Section: Composition Of the Fibersmentioning
confidence: 99%
“…In order to distinguish the different types of water present in the zeolites, the TG curves were analyzed according to the procedure outlined in the literature. [2] The low-temperature inflection point was observed at around 100 C for NZ. The rapid weight loss up to this temperature (4.4% w=w) was due to desorption of the externally adsorbed water.…”
Section: Thermogravimetric Analysismentioning
confidence: 97%
“…Dehydration behaviors of clinoptilolite have been investigated by various analytical techniques including thermogravimetry (TG), differential thermogravimetry (DTG), differential thermal analysis (DTA), differential scanning calorimetry (DSC), [1][2][3][4][5][6][7][8] infrared spectroscopy, [9] and single-crystal X-ray diffraction, [10] and different types of water were identified in clinoptilolite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation